Nitration Time and Ultrasonic Waves Utilization Effects Against Mol Percentage of Nitrogen in Nitrocellulose Synthetic Based on Cotton Fiber - Mohammad Farid Rahman; I Made Jiwa Astika; Yudhi Dwi Kurniawan; Suratmo Suratmo (Natural B, Journal of Health and Environmental Sciences, 2011)
Nitrocellulose is an ester of nitric acid from cellulose which has important role in propellant manufacture, especially having minimal degree of substitution (DS) of 2.5. The aims of this research were to understand the influence of time of reaction in nitration of cotton fiber both synthesized with and without using ultrasonic wave irradiation to mole percentages of nitrogen in nitrocellulose products. The nitrations were conducted by using mixture of sulphuric acid and nitric acid with mass composition ratio of 3:1 (30 mLs of H2SO4 95-97% (w/w) solution; 20 mLs of HNO3 65% (w/w) solution) for 35, 40, 45, 50 and 55 minutes at temperature of 28-29oC, whereas in irradiation treatment by ultrasonic wave the initial temperature adjusted at the same. The mol percentages of nitrogen in nitrocellulose products were determined by using absorbance ratio method from IR spectra without external calibration prerequisite. The results showed that the mol percentages of nitrogen in nitrocelluloses both synthesized with and without using ultrasonic wave irradiation tended to increase up to about 45 minutes and tended to decrease after it. The highest mole percentage of nitrogen in nitrocellulose product synthesized without using ultrasonic wave irradiation was 33.05% with DS of 0.99; whereas that of using ultrasonic wave irradiation increased to 52.78% with DS of 1.58. The analysis of IR spectra and burning characteristic from nitrocellulose products showed the existence of the NO2 group in nitrocellulose products.